Pengaruh profitabilitas, leverage, likuiditas, struktur modal dan keputusan investasi terhadap nilai perusahaan pada perusahaan sektor keuangan yang terdaftar di Bursa Efek Indonesia Tahun 2015-2017 - Manalu, Peffi; Getsmani, Getsmani; Permatasari Hutagaol, Citra; Arisandy Aruan, Deasy (Jurnal Paradigma Ekonomika, 2021)
This study aims to determine the effect of profitability, leverage, liquidity, capital structure, and investment decisions on firm value. A research approach is a quantitative approach. The study population was taken from financial sector companies that have been listed on the Indonesia Stock Exchange 2015-2017, namely from a total of 87 companies, 39 companies were taken. The sample applies the purposive sampling technique. The research successfully proves that profitability, leverage, liquidity, capital structure, and investment decisions have a positive and significant effect on firm value. Partially, the research results are only profitability which has a positive and significant effect on firm value. So that the Adj obtained. R Square 13.1% with the remaining 86.9% influenced by outside variables. Â